2005
DOI: 10.1080/15376520590918766
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Modulation of Oxidative Stress

Abstract: Statins inhibit the activity of a rate-limiting enzyme in cholesterol biosynthesis, converting 3-hydroxy 3-methylglutaryl coenzyme A to mevalonate, and are widely used in the treatment of cardiovascular diseases. Statins decrease the synthesis of cholesterol and other nonsteroid isoprenoids originating from mevalonate, such as farnesyl- and geranylgeranylpyrophosphate, dolichol, and ubiquinone. Recent studies indicate that the beneficial effect of statins on cardiovascular risk also occurs in persons with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 369 publications
1
33
0
14
Order By: Relevance
“…In this model, the balance of oxidized/ reduced form of glutathione influenced I to current density (Rozanski and Xu 2002). As statins are also able to affect this equilibrium (Beltowski 2005), a statin-induced shift of cellular redox state might finally also alter I to in our model.…”
Section: Effects Of Rapid Atrial Pacing And/or Atorvastatin Treatmentmentioning
confidence: 98%
“…In this model, the balance of oxidized/ reduced form of glutathione influenced I to current density (Rozanski and Xu 2002). As statins are also able to affect this equilibrium (Beltowski 2005), a statin-induced shift of cellular redox state might finally also alter I to in our model.…”
Section: Effects Of Rapid Atrial Pacing And/or Atorvastatin Treatmentmentioning
confidence: 98%
“…Importantly, statins are able to pass through BBB and exert a number of pleiotropic activities that might underlie their antidepressant efficacy. It has been found that statins increase the availability of tryptophan by inhibiting IDO (Kilic et al, 2012) and exert antioxidant properties (Beltowski, 2005). Additionally, statins might be involved in inflammatory processes (Antonopoulos et al, 2012).…”
Section: Statinsmentioning
confidence: 99%
“…Many chemopreventive agents appear to target signaling intermediates in apoptosis-inducing pathways (Sun et al, 2004) and are found to be antioxidant (Giacosa et al, 1997). Lovastatin has been reported to possess proapoptotic (Chan et al, 2003) and antioxidant activities (Beltowski, 2005). Hence the demonstrated antimutagenic activity of lovastatin and atorvastatin supports their possible therapeutic application as cancer chemopreventive agents.…”
Section: Discussionmentioning
confidence: 90%